Soil strength and slope stability - Duncan, J. M. (John Wiley & Sons Inc., 2014)
The definitive guide to the critical issue of slope stability and safety Soil Strength and Slope Stability, Second Edition presents the latest thinking and techniques in the assessment of natural and man-made slopes, and the factors that cause them to survive or crumble. Using clear, concise language and practical examples, the book explains the practical aspects of geotechnical engineering as applied to slopes and embankments. The new second edition includes a thorough discussion on the use of analysis software, providing the background to understand what the software is doing, along with sev.